2020
DOI: 10.1128/jvi.02187-19
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus Small T Antigen Induces Apoptosis in Mammalian Cells through the UNC5B Pathway in a PP2A-Dependent Manner

Abstract: UNC5B is a dependence receptor that promotes survival in the presence of its ligand, netrin-1, while inducing cell death in its absence. The receptor has an important role in the development of the nervous and vascular systems. It is also involved in the normal turnover of intestinal epithelium. Netrin-1 and UNC5B are deregulated in multiple cancers, including colorectal, neuroblastoma, and breast tumors. However, the detailed mechanism of UNC5B function is not fully understood. We have utilized the murine pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Addition of doxycycline causes the expression of PyST in these cells and leads to the appearance of a remarkable rounding up phenotype within 16 to 20 h, a feature usually associated with cells undergoing mitosis ( 31 , 32 ). Prolonged induction of small T expression (>24 h) leads to the initiation of apoptosis, which kills most of the cells within 48 h ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of doxycycline causes the expression of PyST in these cells and leads to the appearance of a remarkable rounding up phenotype within 16 to 20 h, a feature usually associated with cells undergoing mitosis ( 31 , 32 ). Prolonged induction of small T expression (>24 h) leads to the initiation of apoptosis, which kills most of the cells within 48 h ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the expression of PyST causes down-regulation of DBC1, it meant that PyST expressing cells would have higher amounts of TRB3 mRNA and hence reduced the phosphorylation of AKT1 at S473. We had previously performed whole genome microarray analysis on mRNAs obtained from the inducible PyST expressing cells (pTREX-PyST-HA-Flag), using Human Genome U133 Plus 2 Array ( 4 ). Microarray data revealed that PyST expressing cells (+dox) had about 2.8 fold increase in TRB3 mRNA levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sT and large T antigen (LT) of SV40, merkell cell polyomavirus (MCV), or Murine polyoma virus (Py) are alternatively-spliced oncoproteins which play a role in the transformation of infected cells ( Rundell and Parakati, 2001 ; Yu et al., 2001 ; Kwun et al., 2009 ). This property of sT, however, is fully reliant on its binding to the scaffold subunit of PP2A ( Yang et al., 1991 ; Ruediger et al., 1992 ), which displaces the regulatory subunit ( Pallas et al., 1990 ; Chen et al., 2004 ) and therefore inhibits PP2A-mediated dephosphorylation of many substrates (with the known exception of histone H1) and promotes viral (DNA) replication ( Scheidtmann et al., 1991 ; Sablina et al., 2007 ; Kwun et al., 2009 ; Bollag et al., 2010 ; Bhat et al., 2020 ). A close dissection of this interaction has been made possible through the crystal structure of the SV40 sT in complex with the Aα subunit of PP2A ( Cho et al., 2007 ).…”
Section: Pp2a Is Ubiquitously Targeted and Modulated By Virusesmentioning
confidence: 99%
“…Examples include the E7 protein of human papillomaviruses (HPV) ( Pim et al., 2005 ) or the leader protein (EBNA-LP) encoded by the Epstein-Barr virus (EBV) ( Garibal et al., 2007 ). At the same time, other viruses target PP2A to drive apoptosis, such as the E4orf4 protein of adenovirus ( Kleinberger and Shenk, 1993 ) and the Py sT-antigen ( Bhat et al., 2020 ).…”
Section: Pp2a Is Ubiquitously Targeted and Modulated By Virusesmentioning
confidence: 99%